1997
DOI: 10.1074/jbc.272.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-mediated Regulation of Interaction of Vibrio cholerae Hemolysin with Erythrocyte and Phospholipid Vesicle

Abstract: Vibrio cholerae hemolysin is an extracellular pore-forming monomeric protein with a native molecular weight of about 60,000. In this study, we showed that the hemolysin interacted with immobilized phospholipids and cholesterol and formed oligomers in vesicles constituted from phospholipids alone with a stoichiometry identical to those produced in rabbit erythrocyte membrane. However, the hemolysin bound to glycoproteins with terminal beta1-galactosyl residues and an association constant of 9.4 x 10(7) M(-1) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 39 publications
7
72
0
Order By: Relevance
“…The VCC protoxin (17) consists of a core cytolytic domain containing the single prestem (pore-forming) loop, an amino-terminal 15-kDa prodomain, and two carboxyl-terminal domains with lectin-like folds that may aid in binding to carbohydrate receptors (18). Functional studies indicate that proteolytic activation must first occur within a consecutive string of protease sites that connect the prodomain to the toxin core (19).…”
mentioning
confidence: 99%
“…The VCC protoxin (17) consists of a core cytolytic domain containing the single prestem (pore-forming) loop, an amino-terminal 15-kDa prodomain, and two carboxyl-terminal domains with lectin-like folds that may aid in binding to carbohydrate receptors (18). Functional studies indicate that proteolytic activation must first occur within a consecutive string of protease sites that connect the prodomain to the toxin core (19).…”
mentioning
confidence: 99%
“…The HlyA monomer and oligomer were purified from a non-O1 V. cholerae strain V 2 as described before (2,8).…”
Section: Immunogenmentioning
confidence: 99%
“…In contrast, the HlyA oligomer (2), though recognized by the same TLR, results in nuclear translocation of NF-κB and induction of IgA. In this paper, we evaluated B-1a cell proliferation, expression of B cell activation marker CD25 (3), and upregulation of the costimulatory molecules, CD80-CD86, as hallmark of cell activation and prelude to HlyA oligomer-induced IgA response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it also seems reasonable to propose that cholesterol is a binding site for VCH. However, it has been shown that VCH also binds to saccharides (21), glycophorin B (27), and sphingolipids (32), respectively, present on target membranes; this suggests that target membranes have multiple binding components for the VCH molecule.…”
mentioning
confidence: 99%